Uma doce melodia: uma proposta de educação musical através da flauta doce no Centro de Ensino Integral Professora Joana Batista Santos Silva em São Luís - Maranhão - BOGÉA, Diego Ted Rodrigues (2018)
ABSTRACT This work deals with musical education through the teaching of sweet flute for young people of the Integral Teaching Center Prof.ª Joana Batista Santos Silva. In general, the text describes, historically, the construction of the flute instrument, its structural, mechanical and sound characteristics as well as the first initiatives of the instrument teaching in Brazil and indicates its applicability in the classroom. The flute was analyzed as a pedagogical instrument as well as peculiar characteristics such as its low cost, its simple handling and a repertoire that goes through several periods of the history of music which comes to potentialize the work of the musical educator with its students. Thus, for these and other aspects highlighted in the body of work, the flute is a viable possibility for the teaching of music and corresponds to a consistent work proposal for the Full Time Teaching Centers of the state public network of Maranhão. For this work to focus on musical learning through the collective teaching of flute in the school space, is based on the researches of Junior, Lorenzo and Tourinho (2009), Tourinho (2007); Cruvinel (2005), Galindo (2000) Oliveira (2011) and Taets (2012). The results of this initiative were weighted through participant observation, field diary and audiovisual record. In this way, we hope that this research will promote new perspectives for music education and also contribute to the democratization of music teaching in Brazilian schools.